A rare occurrence of adenomatoid odontogenic tumor arising from cystic lining in the mandible: Review with a case report - Harish Saluja; Vikrant Kasat; Prafful Gaikwad; Uma Mahindra; Vipin Dehane (Wolters Kluwer Medknow Publications, 2013)
Adenomatoid odontogenic tumor (AOT) is a rare tumor generally found in young females. It is more commonly seen in anterior maxilla in association with an unerupted tooth. Dentigerous cyst is a odontogenic cyst commonly seen arising from the impacted mandibular third molars. We present a case of simultaneous occurrence of both these lesions. A female in the second decade of life reported with the complaint of swelling in the anterior region of lower jaw. Clinical and radiographic findings were suggestive of a dentigerous cyst. Cystic lesion was enucleated and the specimen was sent for histopathologic analysis. It showed AOT in association with a dentigerous cyst. This case is worth discussing as it is rare to find the simultaneous occurrence of two pathologies in the same region of jaw. The common site for AOT is anterior maxilla and for dentigerous cyst is posterior mandible. But in our case, it was found in the anterior mandible in association with an impacted canine.